(untitled) (Sains Humanika, 2010)
This research aims to investigate the effectiveness of e–suara in helping special education students categorized as learning disabilities in answering examination questions without changing the content or quality of the questions. The alternative evaluation carried out in this research was computeraided which was a transformation from the conventional paper–and–pencil approach. A total of 163 special education form two students nationwide were selected as sample in the research. They were divided into three groups; (1) group of students who answered the examination questions by using the conventional method; (2) students who answered the examination questions by using the e–suara I method, that is seeing and reading and listening to the examination questions through computer but answered the questions by using the conventional method; and (3) group of students who used e–suara II method that is seeing/reading and listening to examination questions and answered using the computer. Findings show that students who answered questions using the e–suara II method performed better in the examination with min score of 8.35 compared to the other two groups. Generaly, e–suara method can help special education students to answer examination question better than the conventional method.